The use of parent participation in family centred care - Howard, Alice (2011)
The importance of parental presence, their knowledge, understanding and involvement in care, is now widely acknowledged to result in holistic improvement and wellbeing of the child and family. The concept of Family Centred Care (FCC) supports this development; however, acknowledgement of the importance of Parent Negotiation (PN) requires more research. The need and effect of effective establishment of a collaborative relationship which allows effective communication, discussion and negotiation is less certain, and investigation into the causes and barriers of implementation is required. The literature available is dated, and considering the development of children’s nursing recently, a better understanding of PN is needed within the context of today’s health care system and society. This study utilises a qualitative methodology, interviewing 11 participants (5 parents of children who have experienced hospitalisation, and 6 qualified children’s nurses), with the aim of exploring their perceptions and understandings of PN. The interviews were analysed thematically, and themes extracted were discussed in relation to the surrounding literature and wider context. This study provided further discussion for issues already raised by previous literature, highlighting that, despite previous acknowledgement, there is little evidence that these issues have been ameliorated. It also provides discussion of issues which have received little attention in the past, and therefore provide a sound platform for future research in this area. In conclusion, the understanding and knowledge of all individual involved in care planning needs to be considered. Nurses have an accurate and refined understanding of their role, the parent’s role and their involvement. This is not reflected in the parents understanding of this issue, who instead portray confusion and lack of confidence when situated in the unfamiliar and frightening hospital environment. Better education and support of PN, for nursing staff (both pre- and post-registration), will eliminate misconceived preconceptions and expectations, increase understanding of PN, and its benefits and therefore promoting positive and productive collaborative relationships, which encourage efficient communication, discussion, negotiation and renegotiation.